Determination of pollen viability and in vitro pollen germination of Rosa dumalis and Rosa villosa - Ercisli, Sezai (Bangladesh Journal of Botany, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Pollen quantity, viability and germination of four genotypes of Rosa dumalis and R. villosa were investigated. The number of anthers per flower were 90.3 in genotype 4 (Rosa villosa) and 116.4 in genotype 1 (Rosa dumalis). Genotype 1 showed the highest pollen viability on the basis of both TTC and IKI tests. Â Key words: Dogrose, Pollen germination, Pollen viability, Rosa spp. DOI = 10.3329/bjb.v36i2.1511 Bangladesh J. Bot. 36(2): 185-187, 2007 (December)